2004
DOI: 10.1161/01.hyp.0000111834.03000.e4
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Antioxidant Intervention Improves Myocardial Microvascular Function in Experimental Hypertension

Abstract: Abstract-Hypertension increases oxidative stress, which can impair myocardial microvascular function and integrity.However, it is yet unclear whether long-term antioxidant intervention in early hypertension would preserve myocardial perfusion and vascular permeability responses to challenge. Pigs were studied after 12 weeks of renovascular hypertension without (nϭ8) or with daily supplementation of antioxidants (100 IU/kg vitamin E and 1 g vitamin C, nϭ6), and compared with normal controls (nϭ7). Myocardial pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
52
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 57 publications
3
52
0
Order By: Relevance
“…We have previously shown that this antioxidant combination was effective in decreasing oxidative stress and normalizing vascular function. 1,11 Mean arterial pressure (MAP) was measured in all animals by a PhysioTel telemetry system (Data Sciences) implanted at baseline in the left femoral artery. 10 After 12 weeks of observation, the animals were anesthetized (ketamine 17.5 mg/kg/h and xylazine 2.3 mg/kg/h in saline), and catheters were placed in the right atrium for electron beam CT (EBCT) scanning.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that this antioxidant combination was effective in decreasing oxidative stress and normalizing vascular function. 1,11 Mean arterial pressure (MAP) was measured in all animals by a PhysioTel telemetry system (Data Sciences) implanted at baseline in the left femoral artery. 10 After 12 weeks of observation, the animals were anesthetized (ketamine 17.5 mg/kg/h and xylazine 2.3 mg/kg/h in saline), and catheters were placed in the right atrium for electron beam CT (EBCT) scanning.…”
Section: Methodsmentioning
confidence: 99%
“…1 Initially, 40 consecutive ECGtriggered end-diastolic scans were acquired at 1 to 3 heartbeat intervals after a bolus injection of the contrast medium iopamidol (0.5 mL/kg over 2 seconds). After a 15-minute recovery, the flow study was repeated toward the end of a 15-minute infusion of adenosine (400 g/kg/min).…”
Section: Ebct Scanningmentioning
confidence: 99%
See 1 more Smart Citation
“…Regional myocardial perfusion, [15][16][17] cardiac output, and stroke volume (SV; cardiac output/heart rate) were calculated as others 19 and we 20 have previously shown. In 10 of the 36 animals, the EBCT scanner was also used in cine mode for geometric analysis of LV dynamics.…”
Section: Ebct Data Analysismentioning
confidence: 99%
“…However, it has been shown that myocardial microvascular permeability can change under various pathologic and metabolic circumstances such as diabetes mellitus (24,41), hypercholesterolemia (32), hypertension (31), and acute myocardial ischemia followed by reperfusion (29). Embolization of microscopic plaque debris into the distal coronary bed during coronary interventions is a common and frequent event (9,10,35) that might be associated with microinfarctions and with adverse clinical outcome (7,10).…”
mentioning
confidence: 99%